AN INTERNATIONAL COLLABORATIVE EDUCATIONAL EFFORT BETWEEN THE UNIVERSITY OF MARYLAND, THE UNIVERSITY OF DELAWARE AND ZAPOROZHYE NATIONAL UNIVERSITY - Palley, Howard A.; Palley, Marian L. (Педагогічні науки: теорія та практика, 2007)
The experience of mutual specialists’ study in the sphere of social pedagogic and social work is depicted in the article. The technologies of work in gender, public health (cancer and elderly people supportment). In the sphere of social police (family consulting, sex minority’s representatives).